2014
DOI: 10.1002/2014jc009937
|View full text |Cite
|
Sign up to set email alerts
|

Dense intermediate water outflow from the Cretan Sea: A salinity driven, recurrent phenomenon, connected to thermohaline circulation changes

Abstract: Data collected from different platforms in the Cretan Sea during the 2000s decade present evidence of gradually increasing salinity in the intermediate and deep intermediate layers after the middle of the decade. The observed gradual salt transport toward the deeper layers indicates contributions of dense water masses formed in various Aegean Sea subbasins. The accumulation of these saline and dense water masses in the Cretan Sea finally led to outflow from both Cretan Straits, with density greater than typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
76
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 79 publications
(109 reference statements)
11
76
0
Order By: Relevance
“…The alternating capability of the Cretan and Adriatic seas in producing dense water by means of the internal salt redistribution between the Ionian Sea and Levantine basin has already been pointed out by Gačić et al (2011), and Velaoras et al (2014). Our comparative analysis also suggests that the evolution of thermohaline proper- ties of the two potential dense water source areas is subject to the complex interactions among preconditioning, air-sea interactions, and local dynamics and circulation.…”
Section: Long-term Variability In the Eastern Mediterraneansupporting
confidence: 69%
See 1 more Smart Citation
“…The alternating capability of the Cretan and Adriatic seas in producing dense water by means of the internal salt redistribution between the Ionian Sea and Levantine basin has already been pointed out by Gačić et al (2011), and Velaoras et al (2014). Our comparative analysis also suggests that the evolution of thermohaline proper- ties of the two potential dense water source areas is subject to the complex interactions among preconditioning, air-sea interactions, and local dynamics and circulation.…”
Section: Long-term Variability In the Eastern Mediterraneansupporting
confidence: 69%
“…This reversal is driven by and responsible for internal mass redistribution within the EM. In particular, it seems mainly driven by variability in salinity (Gačić et al, 2011;Theocharis et al, 2014;Velaoras et al, 2014). Wind stress and other external forces play an important role as they interact with the abovementioned processes to shape the variability (strengthening or weakening) of the surface circulation regime and of the sub-basin ocean structures (Molcard et al, 2002;D'Ortenzio and Prieur, 2012;Pinardi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Increased S in one of these basins acts as a DWF preconditioning factor locally, while at the same time a lower salt content in the competitive basins hinders DWF processes therein. Indeed, outflow of denser than usual CIW from the Cretan Sea was observed during the high salinity period (2008)(2009)(2010) in that basin Velaoras et al, 2014), while dense water was formed in the Adriatic Sea during the high salinity period (winter 2012) in the Adriatic Sea (Gačić et al, 2014). It is therefore clear that the understanding of such oscillations and their implications on the preconditioning factors of the two DWF areas of the EMed provides important foresight on future DWF events.…”
Section: Discussionmentioning
confidence: 95%
“…In particular, Gačić et al (2010Gačić et al ( , 2011Gačić et al ( , 2013 have proposed a feedback mechanism induced by the Adriatic dense water production, named the Adriatic-Ionian Bimodal Oscillating System (BiOS), which can influence the salt distribution in the whole EMed. Additionally, Theocharis et al (2014) and Velaoras et al (2014) have suggested the existence of an internal thermohaline pumping mechanism that takes into account the whole upper thermohaline cell of the EMed, which regulates the salinity distribution and the DWF processes in the respective formation areas of the EMed. Both aforementioned theories attribute the circulation oscillations to internal thermohaline mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The Cretan Sea exchanges water masses with adjacent EMed basins and acts as a large heat and salt repository that accumulates water masses originating from various Aegean Sea sub-basins (Theocharis et al, 1993;Velaoras et al, 2014). Furthermore the Cretan Sea itself is an active intermediate and occasionally deep water formation basin.…”
Section: Introductionmentioning
confidence: 99%